Construction of a collection of introgression lines of "Texas" almond DNA fragments in the "Earlygold" peach genetic background. Issue 1 (23rd March 2022) - Kalluri, Naveen; Serra, Octávio; Donoso, José Manuel; Picañol, Roger; Howad, Werner; Eduardo, Iban; Arús, Pere
Abstract: Peach [ Prunus persica L. Batsch] is one of the major temperate fruit tree species, the commercial materials of which have a low level of genetic variability. Almond [ P. dulcis (Mill) DA Webb], a close relative of peach cultivated for its kernels, has a much higher level of diversity. The species are inter-compatible and often produce fertile hybrids, almond being a possible source of new genes for peach that could provide biotic and abiotic stress tolerance traits. In this paper we describe the development of a collection of peach-almond introgression lines (ILs) having a single fragment of almond (cv. Texas) in the peach background (cv. Earlygold). Lines with few introgressions were selected with markers from successive generations from a "Texas" × "Earlygold" F1 hybrid, initially using a set of SSRs and later with the 18 k peach SNP chip, allowing for the final extraction of 67 lines, 39 with almond heterozygous introgressions covering 99% of the genome, and 28 with homozygous introgressions covering 83% of the genome. As a proof of concept, four major genes and four quantitative characters were examined in the selected ILs giving results generally consistent with previous information on the genetics of these characters. This collection is the first of its kind produced in a woody perennial species and promises to be a valuable tool for genetic analyses, including dissection of quantitative traits, positional cloning, epistasis and as prebreeding material to introgress almond genes of interest into the peach commercial gene pool.